How International Tax Practices Shape Earnings Quality: The Moderating Role of Tax Risk Management in Southeast Asia - Tirta Prasetya Dilaga; Hubertus Ade Resha Raditya Boli (Jurnal Ekonomi, Akuntansi, dan Perpajakan, 2025)
This study examines the influence of international tax practices (measured by transfer pricing) and tax risk management (measured by effective tax rate) on corporate earnings quality (measured by earnings persistence). It also investigates the moderating role of tax risk management in the relationship between international tax practices and earnings quality. Utilizing panel data and multiple linear regression analysis on 650 firm-year observations from manufacturing companies listed on the Indonesia Stock Exchange, Bursa Malaysia, Philippine Stock Exchange, and Singapore Exchange, this study finds that tax risk management has a positive effect on earnings quality. However, the results do not provide sufficient evidence to support the hypothesized association between international tax practices and earnings quality, nor do they confirm a moderating effect of tax risk management in this relationship. These findings suggest that while tax risk management is an important factor considered by firms in maintaining consistent and persistent earnings, its role may not be sufficient to alter the influence of international tax strategies on earnings quality.